2021
DOI: 10.3390/ma14133682
|View full text |Cite
|
Sign up to set email alerts
|

Ethoxylated Butoxyethanol-BADGE Adducts—New Potential Migrants from Epoxy Resin Can Coating Material

Abstract: The acetonitrile extracts of can-coating materials have been analyzed by using high-pressure liquid chromatography/electrospray ionization-mass spectrometry (HPLC/ESI-MS). On the basis of detected ions [M + H]+, [M + NH4]+, [M + Na]+ and product ions, the ethoxylated butoxyethanol-bisphenol A diglycidyl ether adducts were identified in two of the analyzed extracts. Although the oxyethylene unit-containing compounds are widely used for the production of different kinds of materials, the ethoxylated species have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Berger and Oehme (2000) identified the BuOEtOH-BADGE adducts in the extracts of a BADGE-based can which was obtained directly from a food can factory in Switzerland [28]. BuOEtOH-BADGE adducts have also been detected in a few extracts of some food can coatings [35,36]. Lestido-Cardama et al have tentatively identified BuOEtOH-BADGE adducts in one beverage can coating [37].…”
Section: Detection Of Badge-buoetoh Adducts Bamge + Buoetoh and Cyclo...mentioning
confidence: 99%
“…Berger and Oehme (2000) identified the BuOEtOH-BADGE adducts in the extracts of a BADGE-based can which was obtained directly from a food can factory in Switzerland [28]. BuOEtOH-BADGE adducts have also been detected in a few extracts of some food can coatings [35,36]. Lestido-Cardama et al have tentatively identified BuOEtOH-BADGE adducts in one beverage can coating [37].…”
Section: Detection Of Badge-buoetoh Adducts Bamge + Buoetoh and Cyclo...mentioning
confidence: 99%
“…2-Butoxyethanol or ethylene glycol monobutyl ether is a highly water-soluble ether and has low vapour pressure [22]. This compound mainly does not occur naturally, but produced by oxidation of butanol with ethylene oxide [23]. After distillation process, 2-butoxyethanol is the main component of skunk cabbage oil [24].…”
Section: A Essential Oil Extractionmentioning
confidence: 99%
“…Among these studies, the strategy of employing monomers possessing several oxyalkylene units has been widely examined. For example, various kinds of Jeffamines, amine‐terminated polyoxypropylenes, were used to toughen epoxy thermosets 10–15 . For this purpose, some epoxy resins like diglycidyl ethers of polyethylene glycol (PEG) and polypropylene glycol were also investigated 16–20 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, various kinds of Jeffamines, amine-terminated polyoxypropylenes, were used to toughen epoxy thermosets. [10][11][12][13][14][15] For this purpose, some epoxy resins like diglycidyl ethers of polyethylene glycol (PEG) and polypropylene glycol were also investigated. [16][17][18][19][20] Employing polyoxyalkylenecontaining monomers, however, reduces the mechanical strength of the resulting cured material.…”
Section: Introductionmentioning
confidence: 99%